STUDI IMPLEMENTASI KEBIJAKSANAAN DIKLATAPARATUR PEMERINTAH DAERAH (KASUSPROGRAM DIKLAT STRUKTURAL ADUM DAN ADUMLA DI DIKLAT PROPINSI DIY) Policy Implementation of The Regional GovernmentApparatus Training: A Case Study - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The ADUM (Administrasi Umum) and ADUMLA (Administrasi Umum Lanjutan) Structural Training Program at the Training Centre of the Special Region of Yogyakarta are parts of Regional Government Apparatus Program in the InWmal Affairs Department The purpose of the Structural Training Program is to increase and develop the knowledge, skill, attitude, personality, and leadership of the officials by educating and training the state officials who are potentials and showing an achievement to occupy the five degree func- tions (for SEPADA/ AMA,' Training) and the five degree officialswho are potentials and showing an achievement to accupy the four degree functions (for SEPALA/ADUMLA Training). The variables being analysed. are Communication, Resources, and Dispotition/ Executor's Attitudes. The research is a descriptive and qualitative research. The data is collected through interview, that is Guided Interview and In-depth interview. The result of the research shows that the Implementation of the ADUM and ADUMLA Structural Training Program at the Training Centre of the Special Region of Yogyakarta has succesfully held the SEPADA/ADUM Structural Training and the SEPALA/ ADUMLA Structural Training. Because of the presence of communication, the implementation of ADUM and ADUMLA Structural Training Program can be done smoothly. The resources variable is seen from the number of the Training Centre officials and their abilities. The executors' attitudes are one of the factors influencing the ADUM and ADUMLA training program implementation. The executors obedience to some decisions and criteria of the training participant give contribution to the success of the ADUM and ADUMLA structural training program implementation.